Profile of Humoral Immunity and B Cell Pool in Infection with the SARS-CoV-2 Prototype Strain and AZD1222 (ChAdOx nCoV-19) Vaccination - Débora Familiar-Macedo; Elzinandes Leal de Azeredo; Elba Regina Sampaio de Lemos; Paulo Vieira Damasco; Luzia Maria de-Oliveira-Pinto (Vaccines)
Background/Objectives: Understanding the behavior of B cells during infection and vaccination is important for determining protective humoral immunity. We evaluated the profile of humoral immunity and B cell pool in individuals who were acutely infected with SARS-CoV-2, recovered from COVID-19, or received two doses of the AZD1222 vaccine. Methods: Peripheral blood mononuclear cells (PBMCs) from these individuals were subjected to in vitro stimulation to promote the differentiation of B cells into antibody-secreting cells (ASCs), and the ELISpot evaluated the abundance of pan and SARS-CoV-2 Spike S1-reactive IgG+ ASC. Stimulated PBMCs were characterized using flow cytometry. Culture supernatants were assessed for soluble B-cell-activating factors. The IgA and IgG for the S1 were evaluated through ELISA. Results: The recovered individuals displayed a robust S1 ASC compared to acute and vaccinated individuals. Although the frequency of total B cells or B cell subsets did not vary among the groups, plasmablast cells were increased in naïve and double-negative B cells in the acute, recovered, and vaccinated individuals. Similar IgA and IgG production appeared to be present in the acute and recovered individuals. During vaccination, more IgG is produced than IgA. In acute patients, BAFF levels were positively correlated with total B cells and IgG+ plasmablast cells but negatively correlated with IgA+ plasmablast cells. Conclusions: Vaccination and natural infection with COVID-19 induce a differential profile and functionality of B cells. We suggest that new vaccines against COVID-19 incorporate molecular adjuvants that regulate B lymphocyte functionality and consider the beneficial aspects of the IgA response in addition to IgG.